PERKEMBANGAN MATEMATIKA DALAM FILSAFAT DAN ALIRAN FORMALISME YANG TERKANDUNG DALAM FILSAFAT MATEMATIKA - Lily Parnabhakti; Marchamah Ulfa (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2020)
AbstractMathematics and philosophy have a pretty close relationship, compared to other sciences. The reason, philosophy is the base for learning science and mathematics is the mother of all sciences. There are also those who think that philosophy and mathematics are the mother of all existing sciences. In historical terms, the relationship between philosophy and mathematics experienced a very striking development. The question arises regarding "Is mathematics an abstract science?" "What is the origin of the formation of numbers?" And questions that are difficult to be solved by mathematics itself. Therefore we need a field of science that can bridge and accommodate questions that arise. Therefore, the field of philosophy has emerged which is able to answer matters concerning the history and development of mathematics itself. This research explains some of the problems surrounding what efforts need to be made to overcome the crisis, contradictions and paradoxes in mathematics and answer the basic questions of mathematical philosophy which currently widely used to teach and develop mathematics.Keywords: philosophy mathematics, evolution of mathematics